Design and evaluation of a two-section canopy shaker with variable frequency for mechanical harvesting of citrus - Pu, Yingjun; Toudeshki, Arash; Ehsani, Reza; Yang, Fuzeng (International Journal of Agricultural and Biological Engineering, 2018)
Canopy shaking is one of the most commonly used techniques for mechanical harvesting of citrus fruits in orange juice industry. However, tree damage and low harvesting efficiency are the top concerns of growers in adopting the existing harvesting equipment on a large scale. The purpose of this research was to develop a novel canopy shaking system to minimize tree damage and maximize fruit removal for mechanical citrus harvesting. In this study, a two-section canopy shaker composing of top and bottom shaking systems mounted on two rotating drums was proposed and developed. It was configured with two sets of flexible bow-shaped shaking rods in a staggered distribution, which can shake the top and bottom zones of the tree canopy independently. The shaking system was designed based on a linked crank-rocker mechanism. Kinematic simulation analysis was conducted to verify the quick return characteristics and differential properties of this mechanism. Vibration test showed that the frequency of the shaking rod could be adjusted within a range of 1.1-8.8 Hz related to hydraulic motor speeds. The field tests of the shaking system with an average frequency of 4.7 Hz achieved a fruit removal percentage of 82.6% and tree damage rate of 5.4% under a tractor speed of 3 km/h. By contrast, the combined shaking frequency of 4.7 Hz & 4.1 Hz of the canopy shaker produced less tree damage with a percentage of 3.9%. This study indicated that the two-section canopy shaker with an optimized frequency combination could be adaptable to the different zones of the tree canopy, and obtain lower tree damage and higher fruit removal percentage.Keywords: two-section canopy shaker, crank-rocker mechanism, variable frequency, fruit removal percentage, tree damage rate, citrus mechanical harvestingDOI: 10.25165/j.ijabe.20181105.4445Citation: Pu Y J, Toudeshki A, Ehsani R, Yang F Z. Design and evaluation of a two-section canopy shaker with variable frequency for mechanical harvesting of citrus. Int J Agric & Biol Eng, 2018; 11(5): 77–87.